Impaired arginine/ornithine metabolism drives severe HFMD by promoting cytokine storm - Zhang, Yaozhong; Yang, Qingqing; Peng, Qi; Tian, Zhihua; Lv, Fen; Zeng, Xiaomei; Jiang, Zaixue; Cheng, Qingqiu; Yang, Lijun; Zhong, Baimao; Lu, Xiaomei; Zhu, Yinghua (Frontiers in Immunology, 2024)
The Hand, Foot and Mouth Disease (HFMD), caused by enterovirus 71 infection, is a global public health emergency. Severe HFMD poses a significant threat to the life and well-being of children. Numerous studies have indicated that the occurrence of severe HFMD is associated with cytokine storm. However, the precise molecular mechanism underlying cytokine storm development remains elusive, and there are currently no safe and effective treatments available for severe HFMD in children. In this study, we established a mouse model of severe HFMD and identified disturbances in arginine/ornithine metabolism as a pivotal factor driving cytokine storm onset in severe HFMD cases. Additionally, we discovered that spermine, an ornithine metabolite, effectively mitigated the inflammatory injury phenotype observed in mice with severe HFMD. In conclusion, our findings provide novel insights into the molecular mechanisms underlying severe HFMD from a metabolic perspective while offering a promising new strategy for its safe and effective treatment.